Characterization of Bacillus Cereus Isolated From Readyto-Eat Cereals - Lee, Hai Yen (2009)
Since availability of data on the contamination of spore formers such as B. cereus in ready-to-eat foods is scarce particularly from developing countries, this surveillance was conducted to address the issue. The preliminary findings from this study revealed a high prevalence of B. cereus s.l. being detected using MPN-PCR in 76% of 111 samples of ready-to-eat cereals tested. The range of concentration was from 30 MPN/g to more than 24,000 MPN/g. Results indicated the differences in the level of contamination for B. cereus s.l. in various products based on factors such as product types, ingredients added and location of manufacturer. The highest concentration of B. cereus s.l. was found in samples with ingredients from weaning products which are, product made from vegetable origin. The alarming findings on the high prevalence of B. cereus s.l. in ready-to-eat cereals prompted further studies on the isolates from these samples. Isolation of colonies from these samples were characterized based on toxin gene screening, plasmid profiles, antibiotic resistance and fingerprinted using RAPD-PCR analysis. In addition to the high prevalence in RTE cereals, the toxin screening profile indicated 58% of the isolate carry the Bacillus enterotoxin T (bceT gene) and 34% carries the tri-component non-hemolytic enterotoxin (nhe gene). This shows that majority of the isolates from ready-toeat cereals are diarrheagenic. The plasmid profile revealed one isolate carrying the plasmid size similar to cereulide protein which is responsible for the emetic disease therefore showing the less common prevalence of emetic isolates from RTE cereals. Isolates of B. cereus s.l. were found to be resistant to ampicillin, metronidazole but highly susceptible to antibiotics with mechanism of action that inhibits the protein synthesis such as erythromycin, oxytetracycline, spectinomycin, neomycin, furozolidone, quinopristin/dalfopristin. Even though B. cereus usually manifests a self limiting disease, the emergence of antibiotic resistance bacteria is a major concern worldwide and due to ease of horizontal gene transfer between the subspecies of B. cereus s.l., the risk of other more lethal subspecies such as B. anthracis obtaining the antibiotic resistance gene may also occur. This preliminary finding revealed an interesting risk profile for B. cereus s.l. as there are no known data available for the assessment on the microbiological quality of RTE cereals especially for spore formers. Based on the risk assessment study conducted, an estimate of on worst case scenario showed 48 diarrhea cases in 27 million populations are known to occur per annum from consumption of RTE cereals.